The Concept of Negotiation Obligations Between Banks and Defaulting Debtors Based on the Principle of Good Faith in the Perspective of the Civil Code - Indarta, Didiek Wahju; Mangar, Irma; Juventia Imelda R (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
This study discusses the legal position of banks against defaulting debtors from the perspective of the Civil Code (KUHPerdata), focusing on the absence of a bank's legal obligation to negotiate. The research emphasizes that the Civil Code does not require banks to negotiate before pursuing their legal rights, such as collecting obligations, demanding compensation, or executing guarantees. This study is based on two main legal principles, namely the principle of freedom of contract, which provides space for the parties to determine the content of the agreement including the negotiation clause, and the principle of good faith, which limits the exercise of rights to be carried out in a reasonable and proportionate manner. The research is normative-juridical, analyzing articles of the Civil Code, the Banking Law, and related legal literature, and assessing the juridical implications of the absence of negotiation obligations for banks. The results of this study are expected to provide a conceptual understanding of the rights and obligations of banks and debtors as well as alternative to normative non-performing loans.